Hubungan Dukungan Sosial Teman Sebaya dengan Stres Akademik pada Siswa Kelas XI SMA Darul Ulum 1 Unggulan Peterongan Jombang - Arfin Nurma Halida; amaliarahimkhairunnisa (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the relationship between peer social support and academic stress among senior high school students. The research employed a quantitative correlational design with a cross-sectional approach. Participants consisted of 242 eleventh-grade students, both male and female, selected using a saturated sampling technique. Data were collected using two adapted instruments: the Educational Stress Scale for Adolescents (ESSA) consisting of 16 items to measure academic stress and the Student Academic Support Scale (SSSS) consisting of 14 items to measure peer social support. Descriptive results indicated that peer social support scores ranged from 15 to 70 (SD = 10.91), while academic stress scores ranged from 22 to 80 (SD = 10.29). Normality testing using the Shapiro–Wilk test showed that both variables were normally distributed (p > 0.05), allowing the use of Pearson correlation analysis. The results revealed a significant positive relationship between peer social support and academic stress (r = 0.155, p = 0.016). Although the correlation strength was categorized as weak, the findings indicate that higher peer social support was associated with higher levels of academic stress among students. These findings suggest that peer support may function not only as emotional and academic assistance, but also as a factor that increases students’ awareness of academic expectations and performance demands. Therefore, efforts to manage academic stress should not only enhance peer support but also strengthen students’ coping strategies and emotional regulation to maintain academic well-being.